Marketing analysis of the pharmaceutical market of antidiabetic drugs in Ukraine - A. O. Savych; B. V. Pavliuk (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2022)
Diabetes mellitus is an important public health issue. Statistics show a rapid growth in the number of patients each year, which increases the financial burden on the state’s economy. Therefore, systematic marketing monitoring of the pharmaceutical market of drugs for diabetes is appropriate and permanently relevant.